1990
DOI: 10.1128/iai.58.10.3394-3400.1990
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunization against experimental Bacteroides (Porphyromonas) gingivalis infection

Abstract: The effects of immunization in modulating the pathogenesis of Bacteroides (Porphyromonas) gingivalis infection in a murine model system were examined. BALB/c mice were immunized by intraperitoneal injection with B. gingivalis ATCC 53977 (one injection per week for 3 weeks), or with a lithium diiodosalicylate (LIS) extract (one injection per week for 3 weeks), or with lipopolysaccharide (LPS; one intravenous or intraperitoneal injection) from this same strain. Two weeks after the final immunization, the mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 34 publications
5
53
0
Order By: Relevance
“…In addition, immunization with highly purified P. gingivalis fimbriae was found to be protective against periodontal bone destruction in P. gingivalis-infected gnotobiotic rats (8). On the other hand, Chen et al (3) have reported that immunization with P. gingivalis lipopolysaccharide does not result in readily detectable antibody levels nor does it afford protection from a challenge infection with P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immunization with highly purified P. gingivalis fimbriae was found to be protective against periodontal bone destruction in P. gingivalis-infected gnotobiotic rats (8). On the other hand, Chen et al (3) have reported that immunization with P. gingivalis lipopolysaccharide does not result in readily detectable antibody levels nor does it afford protection from a challenge infection with P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were collected at death and tested for antibody activity to P. gingivalis or A. actinomycetemcomitans by ELISA, as previously described (10). Briefly, 96-well microtiter plates were coated with P. gingivalis or A. actinomycetemcomitans at a cell concentration of OD5go=0.3 (~2xlOVml).…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Serum antibody reactivity to P. gingivalis and A. actinomycetemcomitans was also evaluated by Western immunoblot analysis, as previously described (10). After separation of a P. gingivalis lithium diiodosalicylate extract (10) and a sonicate extract of A. actinomycetemcomitans by sodium dodecyl sulfatepolyacrylamide (12%) gel electrophoresis, the antigens were transferred to nitrocellulose using a semi-dry transfer system (Polyblot transfer apparatus.…”
Section: Western Immunobiot Analysismentioning
confidence: 99%
See 2 more Smart Citations